Current Perspectives in Organization Development - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1974)
This article reviews "Current Perspectives in Organization Development" edited by J. Jennings Partin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z